A New Method for Obtaining the Baryons Mass under the Killingbeck Plus Isotonic Oscillator Potentials - Nasrin Salehi (Advances in High Energy Physics)
The spectrum of ground state and excited baryons (N, Δ, Λ, Σ, Ξ, and Ω particles) has been investigated by using nonrelativistic quantum mechanics under the Killingbeck plus isotonic oscillator potentials. Using the Jacobi coordinates, anzast method, and generalized Gürsey Radicati (GR) mass formula the three-body-wave equation is solved to calculate the different states of the considered baryons. A comparison between our calculations and the available experimental data shows that the position of the Roper resonances of the nucleon, the ground states, and the excited multiplets up to three GeV are in general well reproduced. Also one can conclude that the interaction between the quark constituents of baryon resonances could be described adequately by using the combination of Killingbeck and isotonic oscillator potentials form.